Epstein–Barr Virus-Positive Langerhans Cell Sarcoma: Is There a Link? A Case Report - Guo, Yu; Zhou, Shui-Hong; Cao, Zai-Zai; Bao, Yang-Yang; Shen, Li-Fang; Yao, Hong-Tian (Frontiers in Oncology, 2022)
Langerhans cell sarcoma (LCS) is an extremely rare malignant neoplasm that originates from Langerhans cells (LCs). Fewer than 70 cases have been reported in the English-language literature. LCS has a poor prognosis and requires pathological diagnosis because of the lack of specific clinical manifestations and imaging findings. We report a rare case of LCS with Epstein-Barr virus (EBV) infection; bilateral cervical giant cysts was the initial manifestation. To our knowledge, this is the first report of LCS with EBV infection. The case information was complete and relevant literature was reviewed to gain insight into LCS. The case raises new questions on the oncogenic character of EBV.